Biological Oxidation Reactions – Mechanisms and Design of New Catalysts. Issue 21 (28th July 2015) - Browne, Wesley R.; Nordlander, Ebbe
Abstract: An overview of the papers in this cluster issue is presented. "Biological oxidation reactions utilising dioxygen, superoxide or hydrogen peroxide as oxidants are amongst the most ubiquitous of metal‐catalysed reactions in biology. Over the last four years, the COST action CM1003 'Biological Oxidation Reactions – Mechanisms and Design of New Catalysts' has brought together over 150 researchers from over 18 European countries to exchange ideas and collaborate on answering key questions facing the field." Abstract : An overview of the papers in this cluster issue is presented. "Biological oxidation reactions utilising dioxygen, superoxide or hydrogen peroxide as oxidants are amongst the most ubiquitous of metal‐catalysed reactions in biology. Over the last four years, the COST action CM1003 'Biological Oxidation Reactions – Mechanisms and Design of New Catalysts' has brought together over 150 researchers from over 18 European countries to exchange ideas and collaborate on answering key questions facing the field."